Ultrasonic emulsification and aspiration for coral reef atherosclerosis as a novel alternative to transaortic endarterectomy and thoracic aorta-based bypass grafting - Yamini Vyas, MD; Joshua K. Burk, MD, MBA; Jane M. Chung, MD; Benjamin D. Colvard, MD; Yakov L. Elgudin, MD, PhD; Jae S. Cho, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Transaortic endarterectomy (TE) is an effective and durable method of restoring patency in the aorta afflicted with atherosclerotic disease, which most commonly affects the infrarenal aorta and common iliac artery. When the suprarenal aorta is involved, the disease is usually confined to the orifices of the visceral vessels without obstruction of the aortic lumen. In rare cases, dense, calcified, exophytic, and amorphous lesions causing severe luminal obstruction, termed coral reef atherosclerosis (CRA) of the suprarenal aorta, may occur. Not all CRAs, however, are amenable to TE due to aortic wall plaque erosion and adventitial thinning. Thoracic aorta-based bypass grafting of the visceral vessels is another option if the descending thoracic aorta is clampable. However, like TE, this option may not be viable for all patients due to compromised pulmonary function or comorbidities. We present a novel alternative to TE using a Sonopet ultrasonic aspiration device in patients with CRA.